European Biometric Borders and (Im)Mobilities in West Africa : Reflections on Migrant Strategies for Border Circumvention and Subversion - Iwuoha, Victor (Politics & Policy, 2025)
This article argues that the European biometric ID installations and securitization practices at West African borders harm African migrants and compromise the security goals of Europe and Africa. Using Niger's experience, I contend that migrants' poor adaption to the biometric border processes is closely connected to their identity conflicts, as well as their atomization and weakening of their social integration. The new border security measures are implicated in the state's criminalizing and dehumanizing practices which migrants and borderbrokers experience every day. I coin two concepts, namely, biometric reborderization and agentic deborderization, to draw close attention to ways by which the European biometric projects are significantly reconfiguring African borders. These borders now represent both a dynamic space for migration control, and contested sites of biometric circumvention and subversion by biometric noncompliant migrants who constantly negotiate alternative means for mobilities. Moral mobility agents contest/circumvent European biometric reborderization via the use of parallel border routes. Related Articles Byrne, Jennifer. 2016. “Contextual Identity among Liberian Refugees in Ghana: Identity Salience in a Protracted Refugee Situation.” Politics & Policy 44(4): 751–82. https://doi.org/10.1111/polp.12169. Djeufack Dongmo, Aristophane, and Désiré Avom. 2024. “Urbanization, Civil Conflict, and the Severity of Food Insecurity in Africa.” Politics & Policy 52(1): 140–68. https://doi.org/10.1111/polp.12572. Garrett, Terence M., and Arthur J. Sementelli. 2023. “Revisiting the Policy Implications of COVID-19, Asylum Seekers, and Migrants on the Mexico–U.S. Border: Creating (and Maintaining) States of Exception in the Trump and Biden Administrations.” Politics & Policy 51(3): 458–75. https://doi.org/10.1111/polp.12537.
Keywords: biometric borders; biometric ID; deborderization; digital identity; European externalization strategies; Migration Control; security; West Africa; Fronteras biométricas; identificación biométrica; movilidad; migración; securitización; África Occidental; Níger; reborderización; 生物特征边界; 生物特征ID; 流动性; 迁移; 安全化; 西非; 尼日尔; 再边界化